The supply of foreign talent: How skill-biased technology drives the location choice and skills of new immigrants - Andreas Beerli; Ronald Indergand; Johannes S. Kunz (Global Labor Organization (GLO), 2021)
An important goal of immigration policy is to facilitate the entry of foreignborn workers whose skills are in short supply in national labor markets. In recent decades, information and communication technology [ICT] has fueled the demand for highly educated workers at the expense of lower educated groups. Exploiting the fact that different regions in Switzerland have been differentially exposed to ICT due to their pre-ICT industrial composition, we present evidence suggesting that more exposed regions experienced stronger ICT adoption, accompanied by considerably stronger growth in relative employment and wage-premia for college-educated workers. Following this change in the landscape of relative economic opportunities, we find robust evidence that these regions experienced a much stronger in ux of highly educated immigrants in absolute terms as well as relative to lower educated groups. Our results suggest that immigrants' location decisions respond strongly to these long-run, technology-driven changes in their economic opportunities.
Keywords: F22; J61; J24; J31; J23; 330; immigrant sorting; international migration; skill-biased technical change; information and communication technology; skill supply